2002
DOI: 10.1177/004051750207200607
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Color Classification by Fuzzy Logic

Abstract: This paper describes the application of fuzzy logic to cotton color grading in an attempt to improve the acceptance of machine grading for cotton colors. Cotton color grades are a number of classes in the (Rd, b) color space. Adjacent color classes have blurry and overlapping boundaries, making crisp-boundary methods ineffective for cotton color classification. Fuzzy logic is specialized to deal with uncertainty and imprecision in the decision-making process, and thus offers a new approach for grading cotton c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…There have been a variety of studies conducted on the measurement of the color grade of cotton. 3–8 Past research has studied the relationship between color grade as reported by cotton classifiers and the color properties determined by the early disc colorimeters during the development of cotton color standards. 3 A major focus of previous studies has been on the development of methods or algorithms for improving the measurement of the overall color grade of a cotton sample.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a variety of studies conducted on the measurement of the color grade of cotton. 3–8 Past research has studied the relationship between color grade as reported by cotton classifiers and the color properties determined by the early disc colorimeters during the development of cotton color standards. 3 A major focus of previous studies has been on the development of methods or algorithms for improving the measurement of the overall color grade of a cotton sample.…”
mentioning
confidence: 99%
“…3 A major focus of previous studies has been on the development of methods or algorithms for improving the measurement of the overall color grade of a cotton sample. These studies have included the use of modern techniques such as fuzzy logic to enhance analysis of the color information, 4 as well as applying artificial neural networks to evaluate the impact of impurities such as trash particles. 5 In recent years efforts have been made to use CIE color parameters or to use color spectrophotometers to develop traceable color standards for cotton grading.…”
mentioning
confidence: 99%
“…Finally, the center of gravity 13,14 is used as a defuzzifier to convert the output of fuzzy inference, μC0, into a clear output value y 0 where μC0(yi) is the membership value of y i , which belongs to the fuzzy set C0, and y0 is the MPCI value.…”
Section: Methodsmentioning
confidence: 99%
“…Since the early work of Thomasson (1993), recent studies have attempted to move toward image-based color measurement so that trash particles can be excluded from the color measurement (Lieberman and Siddaiah, 1999;Xu et al, 1997Xu et al, , 2001Xu et al, , and 2002. These attempts have involved commercially available color cameras and scanners adapted to the purpose of cotton color measurement.…”
Section: Literature Reviewmentioning
confidence: 99%